Surface engineering of perovskite oxides as a promotional approach for water-oxidation - Bhatt, Dipti; Kunchala, Ravi K.; Naidu, Boddu S. (Surfaces and interfaces, 2025)
One of the most important subjects in heterogeneous water oxidation catalysis is the sensible design of inexpensive catalysts with high catalytic activity. Herein, the stoichiometric LaXO3 (X=Mn, Fe) perovskite catalysts were made using the citric sol-gel process. The surface of perovskite is selectively etched with acetic acid for improved photochemical and electrochemical water-oxidation activities. In comparison to pristine materials, these surface-modified nanomaterials exhibit twice catalytic activity with lower overpotentials in electrochemical water oxidation. The turnover frequency (TOF) of pristine LMO and LFO is 1.18 × 10–3 and 1.22 × 10–3 s-1, respectively, whereas the values are 2.60 × 10–3 s-1 for LMO-1M, and 2.79 × 10–3 s-1 for LFO-1M. The lower Tafel slope values compared to pristine samples show faster kinetics in the acid-treated samples. The improvement in the oxygen evolution activity is due to the enhanced hydrophilicity, oxygen vacancies, and mixed oxidation states brought about by the partial removal of surface ʻLaʼ ions from pristine perovskites. This study emphasizes how crucial it is to introduce A-site cation shortage in perovskites as a quick and effective way to encourage OER activity. [Display omitted]